Implementasi Model CIRC Dalam Meningkatkan Keterampilan Membaca Pada Soal Tes Kemampuan Akademik - Teguh Juni Hidayat; Hananto Bangun Laksono; Eko Budi Utomo; Wahyu Magribi; Sularsih, Sularsih; Rita Martini (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This study aims to describe the implementation of the Cooperative Integrated Reading and Composition (CIRC) learning model in improving students' reading skills on academic ability test questions, as well as identifying the obstacles faced by teachers in its implementation. The subjects of the study were teachers at Sukoharjo State Islamic Senior High School and Sukoharjo State Islamic Junior High School 3. The informants of this study were teachers. The study used a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. The results showed that the implementation of the CIRC model was carried out through four steps of activities, namely preparation and understanding of the topic (pre-reading), reading activities (reading), writing activities (writing), and post-reading activities (post-reading). These four steps were able to encourage active student involvement, improve text comprehension, and train students' analytical skills in answering academic ability test questions. However, in its implementation, teachers still face several obstacles, namely limited time to implement all stages of CIRC, differences in student ability levels, difficulties in managing group discussions, and limited resources and relevant teaching materials. Based on these findings, it can be concluded that the CIRC model has the potential to improve students' reading skills on academic ability test questions, but it requires careful planning, effective classroom management, and adequate learning resource support so that its implementation can run optimally.